2014
DOI: 10.1007/s00426-014-0615-z
|View full text |Cite
|
Sign up to set email alerts
|

Semantic similarity between old and new items produces false alarms in recognition memory

Abstract: In everyday life, human beings can report memories of past events that did not occur or that occurred differently from the way they remember them because memory is an imperfect process of reconstruction and is prone to distortion and errors. In this recognition study using word stimuli, we investigated whether a specific operationalization of semantic similarity among concepts can modulate false memories while controlling for the possible effect of associative strength and word co-occurrence in an old-new reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 57 publications
8
51
0
Order By: Relevance
“…The present experiments show that density strongly predicts recognition performance and accounts for valence effects; however, it is not clear which of the different components of density influences recognition. As argued earlier, there is good evidence that semantic similarity among stimuli increases false recognition (e.g., Montefinese et al, 2014). However, some researchers have challenged the idea that item noise itself influences recognition performance (e.g., Dennis & Humphreys, 2001;Maguire, Humphreys, Dennis, & Lee, 2010).…”
Section: Limitations and Open Questionsmentioning
confidence: 94%
See 1 more Smart Citation
“…The present experiments show that density strongly predicts recognition performance and accounts for valence effects; however, it is not clear which of the different components of density influences recognition. As argued earlier, there is good evidence that semantic similarity among stimuli increases false recognition (e.g., Montefinese et al, 2014). However, some researchers have challenged the idea that item noise itself influences recognition performance (e.g., Dennis & Humphreys, 2001;Maguire, Humphreys, Dennis, & Lee, 2010).…”
Section: Limitations and Open Questionsmentioning
confidence: 94%
“…This effect appears for stimuli such as alphanumeric characters (Flagg, 1976;Reitman & Bower, 1973), geometric shapes (Medin & Schaffer, 1978;Nosofsky, 1991;Nosofsky, Clark, & Shin, 1989), pictures (Koutstaal & Schacter, 1997;Strack & Bless 1994), faces (Busey & Tunnicliff, 1999;Vokey & Read, 1992), words (Brainerd, Reyna, Mojardin, 1999;Dyne, Humphreys, Bain, & Pike, 1990;Montefinese, Zannino, & Ambrosini, 2014;Postman, 1951;Roediger & McDermott, 1995), and sentences (Cantor & Engle, 1993;Holmes, Waters, & Rajaram, 1998).…”
Section: Density and Memory Performancementioning
confidence: 96%
“…In particular, the data set included the Italian translation of all the English ANEW words (1,034 words) [12] and those from the Italian semantic norms collected in our laboratory (87 words) [59,60] and tested in behavioral [61,62] and psychophysiological [63] studies.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was chosen based on an a-priori power analysis (G*Power 3 software; Faul et al, 2009) for F tests (see Ambrosini et al, 2013;Montefinese et al, 2015a;Montefinese et al, 2015b). This analysis revealed that our sample size was large enough to detect a significant ( = .05)…”
Section: Methodsmentioning
confidence: 99%